1999
DOI: 10.1016/s1074-7613(00)80143-0
|View full text |Cite
|
Sign up to set email alerts
|

Ox40-Ligand Has a Critical Costimulatory Role in Dendritic Cell:T Cell Interactions

Abstract: The tumor necrosis factor family molecule Ox40-ligand (Ox40L) has been identified as a potential costimulatory molecule and also has been implicated in T cell homing and B cell activation. To ascertain the essential functions of Ox40L, we generated and characterized Ox40L-deficient mice. Mice lacking Ox40L exhibit an impaired contact hypersensitivity response, a dendritic cell-dependent T cell-mediated response, due to defects in T cell priming and cytokine production. In contrast, Ox40L-deficient mice do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
207
0
1

Year Published

2000
2000
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(219 citation statements)
references
References 41 publications
11
207
0
1
Order By: Relevance
“…These observations suggest that even low-level T cell priming (ϳ10% of the maximum level) is enough for antibody production. In support of this notion, recent studies showed that antigen-specific T cell proliferation was severely impaired in OX40-deficient mice, although the ability for antibody production remained completely normal in these mutant animals (38,39).…”
Section: Discussionmentioning
confidence: 89%
“…These observations suggest that even low-level T cell priming (ϳ10% of the maximum level) is enough for antibody production. In support of this notion, recent studies showed that antigen-specific T cell proliferation was severely impaired in OX40-deficient mice, although the ability for antibody production remained completely normal in these mutant animals (38,39).…”
Section: Discussionmentioning
confidence: 89%
“…BDC2.5 TCR tg mice (25) were backcrossed for over 25 generations onto the NOD (BDC2.5/N) or the B6.H-2 g7 congenic background that carries the H-2 g7 MHC on the C57BL/6J (BDC2.5/B6 g7 ) background (26), or with the recombinant-activating gene (RAG)-1 KO mutation (over nine generations). Previously described OX40L KO mice (19) were backcrossed onto the NOD/Lt background for eight generations (OX40L o /NOD) and onto B6.H-2 g7 (OX40L o /B6 g7 ) for eight generations, and were intercrossed to obtain animals homozygous for the OX40L mutation. These were crossed with BDC2.5/N and BDC2.5/ B6 g7 , respectively, to generate BDC2.5/N-OX40L o/o and BDC2.5/B6 g7 -OX40L o/o mice (and OX40L-proficient control littermates).…”
Section: Methodsmentioning
confidence: 99%
“…OX40 ligand (OX40L) 4 (CD134-L, tnfsf4) is expressed on APCs, B cells, macrophages, and dendritic cells (DCs), also after activating stimuli (7-10) and on vascular endothelial cells (11). OX40-OX40L costimulation promotes priming and survival of CD4 ϩ T cells after an antigenic or tumor challenge (10,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). It requires direct interaction between T cells and DCs (22), and may involve induction of the anti-apoptotic Bcl-x L and Bcl-2 molecules (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The engagement of OX-40 (CD134) by its ligand OX40L has been shown to deliver a co-stimulatory signal to T cells (45). Studies using OX-40 -/-mice demonstrated that OX-40 was important for the generation of optimal CD4 π T-cell responses in vivo but was not required for the generation of B cells or LCMV-specific primary or memory CTL (46).…”
Section: Ox-40 (Cd134)/ox-40lmentioning
confidence: 99%